Spatio-temporal deformable 3D ConvNets with attention for action recognition. (February 2020) - Li, Jun; Liu, Xianglong; Zhang, Mingyuan; Wang, Deqing
Highlights: We are the first to propose a spatio-temporal deformable 3D convolutions with an attention mechanism (STDA for short). The proposed module serves as a generic module for many 3D CNNs, and in practice it is only needed to append at the later convolution layer without increasing too much computational cost. Our attention mechanism can exploit both long-range temporal dependencies across multiple frames and long-distance spatial dependencies inside each frame, and thus helps extract the discriminative global information at both inter-frame level and intra-frame level. Experiments validate the superior performances and efficiency of the proposed approach. Abstract: The irregularity of human actions poses great challenges in video action recognition. Recently, 3D ConvNet methods have shown promising performance at modelling the motion and appearance information. However, the fixed geometric structure of 3D convolution filters largely limits the learning capacity for video action recognition. To address this problem, this paper proposes a spatio-temporal deformable ConvNet module with an attention mechanism, which takes into consideration the mutual correlations in both temporal and spatial domains, to effectively capture the long-range and long-distance dependencies in the video actions. Our attention based deformable module, as a generic module for 3D ConvNets, can adaptively learn more accurate spatio-temporal offsets to model the action irregularity. The experiments on two popular datasets (UCF-101 and HMDB-51) demonstrate that our module significantly outperforms the state-of-the-art methods.